STRATEGI PROMOSI WISATA KERATON KAIBON DI KELURAHAN KASUNYATAN, KECAMATAN KASEMEN SERANG MELALUI MEDIA SOSIAL UNTUK MENINGKATKAN MINAT PENGUNJUNG - Jesika Hermania Putri; Efrilian Efrilian; Hairiyah Hairiyah; Ade Fauji (Yayasan Education and Social Center, 2026)
This Community Service Program aims to improve the attractiveness of Keraton Kaibon tourism through social media-based promotion strategies in Kasunyatan Village, Kasemen District, Serang City. The main issue identified is the low optimization of digital promotion, resulting in unstable visitor numbers despite the site's high historical and cultural value. The program was implemented in Januari 2026 using a participatory action research approach combined with descriptive qualitative methods. Activities included observation, socialization, digital content creation training, content calendar development, and continuous mentoring of local communities and tourism managers. The results show a significant improvement in community digital literacy, with participants producing more than 200 photos, 15 short videos, and 25 promotional posters distributed through Instagram, TikTok, and Facebook. Social media reach increased to more than 5,000 accounts within two weeks of implementation. In addition, the program positively impacted local micro-economies, as increased tourist visits boosted small vendors’ income around the tourism site. The study concludes that structured and consistent social media-based tourism promotion, supported by community empowerment, effectively enhances tourist interest and strengthens the sustainability of heritage tourism development.